Cobalt-chromium-molybdenum alloy powder for laser cladding and preparation method thereof
By optimizing the chemical composition and preparation methods of cobalt-chromium-molybdenum alloy powder, the existing powder cost, poor fluidity and low spherical rate are solved, and the powder with low cost, high purity and high spherical rate is achieved, which significantly improves the performance of the laser cladding layer and the service life of the product.
Patent Information
- Application Number
- CN202510113885.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
AI Technical Summary
The existing cobalt-chromium-molybdenum alloy powder used for laser cladding has high cost, general fluidity and low spherical rate, which leads to uneven powder feeding during laser cladding, uneven structure of the cladding layer, large porosity, and loose structure, which reduces the performance of the cladding layer and the service life of the product.
By optimizing the chemical composition and preparation methods of cobalt-chromium-molybdenum alloy powder, the cost is reduced, the purity and spherical rate are improved, and the inclusions and oxygen, nitrogen and hydrogen content are reduced. Process steps such as inert gas protection smelting, argon atomization, gas flow grader crushing screening and ultrasonic vibrating screening are adopted.
The low cost, high purity and high spherical rate of cobalt-chromium molybdenum alloy powder are achieved, the fluidity and corrosion resistance of the powder are improved, the uniformity and density of the laser cladding layer are significantly improved, and the service life of the product is extended.
Smart Images

Figure CN119913503A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of powder metallurgy, and in particular to a cobalt-chromium-molybdenum alloy powder for additive manufacturing. Background Art
[0002] Cobalt-chromium-molybdenum alloy has attracted widespread attention for its good weldability, resistance to thermal fatigue, thermal corrosion, wear resistance and thermal strength. At the same time, due to its good biocompatibility and chemical stability, cobalt-based alloys are also used in fields such as biomaterials and new energy. They are even irreplaceable in some harsh environments, such as phosphoric acid pools, nuclear industry, gas turbines, and aerospace.
[0003] Laser cladding is one of the main technologies in the field of additive manufacturing. It is a process in which the selected coating material is placed on the surface of the cladding substrate in the form of different fillers. It is melted simultaneously with a thin layer on the substrate surface by laser irradiation, and then quickly solidified to form a surface coating with extremely low dilution and metallurgical bonding with the substrate material, thereby significantly improving the wear resistance, corrosion resistance, heat resistance, oxidation resistance and electrical properties of the substrate material surface.
[0004] The existing cobalt-chromium-molybdenum alloy powder used as raw material for laser cladding has the following disadvantages: 1. The content of precious metals Co, Cr and Mo accounts for a relatively high proportion, resulting in high cost; 2. The fluidity of cobalt-chromium-molybdenum alloy is average (about 15-18s) and the sphericity rate is low (between 75-90%), which will lead to uneven powder feeding during laser cladding, uneven organization of the cladding layer, large porosity and loose structure, thereby reducing various performances of the cladding layer and shortening the service life of the product after cladding. Summary of the invention
[0005] The problem to be solved by the present invention is to provide a cobalt-chromium-molybdenum alloy powder for laser cladding, which has low cost, high purity, reduced inclusions and oxygen, nitrogen, and hydrogen content in the powder, few inclusions, excellent fluidity, high sphericity, excellent physical properties, especially excellent corrosion resistance, and extended service life of the cladding product. At the same time, the present invention also provides a preparation method of the cobalt-chromium-molybdenum alloy powder.
[0006] The invention discloses a cobalt-chromium-molybdenum alloy powder for laser cladding, the chemical components of which are as follows by mass percentage: Cr: 27.0-32.0%, Mo: 4.0-6.0%, Fe: 7.5-9.5%, Y: 0.4-1.2%, Zr: 0.1-0.4%, and the remainder is Co element and inevitable impurities.
[0007] Among them, the contents of C, S, and P elements in the impurity elements do not exceed 100ppm, the contents of O and N elements do not exceed 80ppm, and the H content does not exceed 10ppm.
[0008] The mass fraction of Y+Zr is preferably: 0.6%≤Y+Zr≤1.1%.
[0009] The mass fraction of Y+Cr is preferably: Y+Cr≥30.0%.
[0010] Among them, the particle size ranges of the cobalt-chromium-molybdenum alloy powder are 45-105μm, 53-150μm, and 75-150μm.
[0011] The invention discloses a method for preparing cobalt-chromium-molybdenum alloy powder, comprising the following steps: (1) smelting under inert gas protection; (2) secondary feeding; (3) argon atomization; (4) crushing and screening by an air flow classifier; and (5) screening by an ultrasonic vibration screen.
[0012] Furthermore, the preparation method comprises the following steps: (1) inert gas protection smelting: high-purity electrolytic cobalt, molybdenum bars, chromium blocks, and pure iron bars are placed in an alumina crucible according to the mass percentage of alloying elements, and then evacuated to a vacuum degree of less than 10 Pa, and the argon gas charging valve is opened until the pressure in the furnace reaches normal pressure to complete the replacement, and the smelting is started after the above operation is repeated twice; (2) secondary feeding: high-purity yttrium is added 10-15 minutes before the furnace is discharged, and high-purity zirconium is added 5-7 minutes before the furnace is discharged; (3) argon atomization: the cobalt-chromium-molybdenum alloy powder is atomized using inert gas argon; (4) air flow classifier crushing and screening: the powder is collected and the powder is Finally, the frequency of the airflow classifier is adjusted, the feeding frequency is 5.0 Hz, the first level is 24.0-28.0 Hz, and the second level is 9.1-11.1 Hz. The airflow classifier uses argon with a purity greater than 99.999%. The airflow classifier is used to screen out the powder of the first level discharge port + 45 μm; (5) Vibrating screen screening: adjust the energy of the ultrasonic controller of the ultrasonic vibrating screen to 100%, select 150 mesh and 325 mesh, 100 mesh and 270 mesh, 100 mesh and 200 mesh screens, pour the coarse powder in the first level discharge port into the vibrating screen discharge port for screening, and the discharge speed is 20 g / s.
[0013] The laser cladding method of cobalt-chromium-molybdenum alloy powder of the present invention has the following process parameters: spot diameter 5mm, laser power 2.4-3.0kW, scanning rate 1100-1500mm / min, powder feeding amount 40-45g / min, and overlap rate 45-60%.
[0014] The advantages of the cobalt-chromium-molybdenum alloy powder for laser cladding of the present invention are as follows: 1. The powder cost is reduced by increasing the proportion of iron elements and reducing the proportions of cobalt, chromium and molybdenum elements; 2. A trace amount of yttrium elements is added for microalloying to reduce the inclusions of oxides such as MnS, Al2O3, MgO and the like and improve the morphology of inclusions, promote the spheroidization of inclusions, and reduce the influence of inclusions on the corrosion resistance of the cladding layer (pitting corrosion on the coating surface generally occurs in the places where inclusions gather); 3. A trace amount of zirconium elements is added to achieve the effects of degassing, fine grains and reduce the size of inclusions: on the one hand, single zirconium can act as a good getter to absorb free oxygen, nitrogen and hydrogen in the alloy liquid, and is added to the alloy liquid to form low-density zirconium oxide floating, which can be easily removed from the alloy liquid slag; on the other hand, the zirconium oxide formed by zirconium oxidation can act as a nucleating agent to achieve the effect of fine grain strengthening during solidification, and at the same time, the size of inclusions (such as Al2O3, MgO, MnS) can be refined, resulting in Cl - It is not easy to invade the matrix and cause corrosion; second, the mass fraction of Y+Zr is preferably: 0.6%≤Y+Zr≤1.1%: if it exceeds this range, the Y2O3 and Zr2O3 formed by the reaction of Y and Zr will have too many inclusions, which are not easy to float up and remove and cause powder pollution; if it is lower than this range, the free oxygen, nitrogen and hydrogen in the alloy liquid cannot be completely removed, resulting in an increase in the oxygen, nitrogen and hydrogen content, and the inclusions are not completely modified, reducing the corrosion resistance of the cladding layer; third, the mass fraction of Y+Cr is preferably: Y+Cr≥30.0%: a higher Cr content is conducive to the formation of Cr2O3 oxide film, improving the corrosion resistance of the cladding layer, and the addition of Y can effectively improve the adhesion of the oxide film, thereby enhancing the high-temperature oxidation resistance and heat corrosion resistance of the cladding layer. The appropriate Y content can also significantly improve the bonding performance of the cladding layer and produce a "pinning" effect.
[0015] The advantages of the cobalt-chromium-molybdenum alloy powder preparation method of the present invention are as follows: 1. A trace amount of yttrium is added 10-15 minutes before the end of the furnace: Since the oxidizing property of single substance yttrium is very strong, it is easy to react with alumina crucibles and other easily oxidized metals such as Cr2O3 to produce burning loss, resulting in component deviation. Therefore, adding single substance yttrium 10-15 minutes before the furnace is conducive to the full homogenization of yttrium (induction melting and self-stirring), and is conducive to the high melting point inclusion Y2O3 formed by the melting of yttrium and oxide. Y2O3 will solidify first and serve as a nucleation point to achieve a fine crystal effect; at the same time, the density of Y2O3 is 5.01g / cm 3 The density of cobalt-chromium-molybdenum alloy is about 8.5g / cm 3, it will fully float up and be removed, thereby reducing the oxygen content in the alloy liquid and achieving the purpose of reducing the oxygen content of the powder: 2. Trace zirconium elements are added 5-7 minutes before the end of the furnace, which helps to reduce the oxidation and burning of zirconium; 3. Argon is used as a protective gas: the density of argon is greater than that of air and nitrogen, and the kinetic energy of the gas is large at the same speed; 4. The first-level frequency in the air flow classification is increased to 24.0-28.0Hz: the frequency of powder collision during air flow classification is increased, and the number of powder satellite powders that are broken is increased. At the same time, the centrifugal force applied to the powder during collision is increased, which is conducive to breaking up satellite powders and special-shaped powders, promoting powder spheroidization, and improving the powder sphericity rate: the air flow classification frequency lower than 24.0Hz will cause incomplete crushing of special-shaped powders and satellite powders, and higher than 28.0Hz will intensify the powder collision, produce pits and breakages on the surface of the micro powder, and increase the number of special-shaped powders.
[0016] In summary, the cobalt-chromium-molybdenum alloy powder prepared by the present invention has high purity, low oxygen, nitrogen and hydrogen content, few inclusions, excellent fluidity, high sphericity and excellent corrosion resistance.
[0017] Instruction Manual
[0018] Figure 1 It is a scanning electron microscope image of the cobalt-chromium-molybdenum alloy powder prepared in Example 1 of the present invention.
[0019] Figure 2 This is a microscopic metallographic structure diagram of the laser cladding coating prepared from the cobalt-chromium-molybdenum alloy powder in Example 1 of the present invention after salt spray corrosion. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below with reference to the embodiments.
[0021] Example 1
[0022] A cobalt-chromium-molybdenum alloy powder has the following chemical components in percentage by weight: Cr: 30.0%, Mo: 4.0%, Fe: 7.5%, Y: 0.4%, Zr: 0.4%, and the remainder is Co element and inevitable impurities; among the impurity elements, the contents of C, S, and P are 49ppm, 23ppm, and 42ppm respectively, the content of O is 53ppm, the content of N is 44ppm, and the content of H is 6ppm.
[0023] The method for preparing the cobalt-chromium-molybdenum alloy powder comprises the following steps:
[0024] (1) Inert gas protection smelting: high-purity electrolytic cobalt, molybdenum bars, chromium blocks, and pure iron bars are placed in an alumina crucible according to the mass percentage of alloy elements, and then evacuated to a vacuum degree of less than 10Pa. The argon gas charging valve is opened until the pressure in the furnace reaches normal pressure to complete the replacement. The above operation is repeated twice before smelting begins.
[0025] (2) Secondary feeding: Add high purity yttrium 15 minutes before the furnace is taken out of the furnace, and add high purity zirconium 7 minutes before the furnace is taken out of the furnace.
[0026] (3) Argon atomization: The cobalt-chromium-molybdenum alloy powder is atomized using inert gas argon.
[0027] (4) Crushing and screening by air classifier: Collect the powder and adjust the frequency of the air classifier. The feed frequency is 5.0 Hz, the first level is 24.0 Hz, and the second level is 9.1 Hz. The air classifier uses argon with a purity greater than 99.999%. The air classifier is used to screen out powder with a size of +45 μm at the first level discharge port.
[0028] (5) Ultrasonic vibration screen screening: adjust the energy of the ultrasonic controller of the ultrasonic vibration screen to 100%, select 150 mesh and 325 mesh screens, use argon gas with a purity greater than 99.999%, pour the coarse powder from the first-level discharge port into the discharge port of the vibration screen for screening, and the discharge speed is 20 g / s.
[0029] from Figure 1 It can be seen that the powder has good surface morphology, high sphericity, uniform particle size, and a small proportion of satellite powder.
[0030] The cobalt-chromium-molybdenum alloy powder obtained in this embodiment was laser clad in two layers on a 100*100 mm 316L test block. The laser cladding process parameters were as follows: spot diameter 5 mm, laser power 2.4 kW, scanning rate 1100 mm / min, powder feeding amount 40 g / min, overlap rate 45%, and a laser cladding layer was obtained.
[0031] from Figure 2 It can be seen that the laser cladding layer has no visible surface defects after salt spray corrosion, and the evaluation level is 0 (best), that is, the Cl- corrosion resistance is excellent.
[0032] Example 2
[0033] A cobalt-chromium-molybdenum alloy powder has the following chemical components in percentage by weight: Cr: 29.5%, Mo: 5.0%, Fe: 8.5%, Y: 0.9%, Zr: 0.1%, and the remainder is Co element and inevitable impurities; among the impurity elements, the contents of C, S, and P are 76ppm, 49ppm, and 27ppm respectively, the content of O is 65ppm, the content of N is 33ppm, and the content of H is 4ppm.
[0034] The method for preparing the cobalt-chromium-molybdenum alloy powder comprises the following steps:
[0035] 1) Inert gas protection smelting: high-purity electrolytic cobalt, molybdenum bars, chromium blocks, and pure iron bars are placed in an alumina crucible according to the mass percentage of alloy elements, and then evacuated to a vacuum degree of less than 10Pa. The argon gas charging valve is opened until the pressure in the furnace reaches normal pressure to complete the replacement. After repeating the above operation twice, smelting begins.
[0036] (2) Secondary feeding: Add high purity yttrium 12 minutes before the furnace is taken out of the furnace, and add high purity zirconium 6 minutes before the furnace is taken out of the furnace.
[0037] (3) Argon atomization: The cobalt-chromium-molybdenum alloy powder is atomized using inert gas argon.
[0038] (4) Crushing and screening by air classifier: Collect the powder and adjust the frequency of the air classifier. The feed frequency is 5.0 Hz, the first level is 26.0 Hz, and the second level is 9.6 Hz. The air classifier uses argon with a purity greater than 99.999%. The air classifier is used to screen out powder with a size of +53 μm at the first level discharge port.
[0039] (5) Ultrasonic vibration screen screening: Adjust the energy of the ultrasonic controller of the ultrasonic vibration screen to 100%, select 100 mesh and 270 mesh screens, and use argon with a purity greater than 99.999%. Pour the coarse powder from the first-stage discharge port into the discharge port of the vibration screen for screening, and the discharge speed is 20g / s.
[0040] The cobalt-chromium-molybdenum alloy powder obtained in this embodiment was laser clad in two layers on a 100*100 mm 316L test block. The laser cladding process parameters were as follows: spot diameter 5 mm, laser power 2.6 kW, scanning rate 1200 mm / min, powder feeding amount 42 g / min, overlap rate 50%, and a laser cladding layer was obtained.
[0041] Example 3
[0042] A cobalt-chromium-molybdenum alloy powder has the following chemical components in percentage by weight: Cr: 32.0%, Mo: 6.0%, Fe: 9.5%, Y: 0.6%, Zr: 0.3%, and the remainder is Co element and inevitable impurities; among the impurity elements, the contents of C, S, and P are 44ppm, 56ppm, and 42ppm respectively, the content of O is 49ppm, the content of N is 23ppm, and the content of H is 5ppm.
[0043] The method for preparing the cobalt-chromium-molybdenum alloy powder comprises the following steps:
[0044] 1) Inert gas protection smelting: high-purity electrolytic cobalt, molybdenum bars, chromium blocks, and pure iron bars are placed in an alumina crucible according to the mass percentage of alloy elements, and then evacuated to a vacuum degree of less than 10Pa. The argon gas charging valve is opened until the pressure in the furnace reaches normal pressure to complete the replacement. After repeating the above operation twice, smelting begins.
[0045] (2) Secondary feeding: Add high purity yttrium 10 minutes before the furnace is taken out of the furnace, and add high purity zirconium 5 minutes before the furnace is taken out of the furnace.
[0046] (3) Argon atomization: The cobalt-chromium-molybdenum alloy powder is atomized using inert gas argon.
[0047] (4) Crushing and screening by air classifier: Collect the powder and adjust the frequency of the air classifier. The feed frequency is 5.0 Hz, the first level is 28.0 Hz, and the second level is 11.1 Hz. The air classifier uses argon with a purity greater than 99.999%. The air classifier is used to screen out powder with a size of +53 μm at the first level discharge port.
[0048] (5) Ultrasonic vibration screen screening: Adjust the energy of the ultrasonic controller of the ultrasonic vibration screen to 100%, select 100 mesh and 200 mesh screens, and use argon gas with a purity greater than 99.999%. Pour the coarse powder from the first-level discharge port into the discharge port of the vibration screen for screening, and the discharge speed is 20g / s.
[0049] The cobalt-chromium-molybdenum alloy powder obtained in this embodiment was laser clad in two layers on a 100*100 mm 316L test block. The laser cladding process parameters were as follows: spot diameter 5 mm, laser power 3.0 kW, scanning rate 1500 mm / min, powder feeding amount 45 g / min, overlap rate 60%, and a laser cladding layer was obtained.
[0050] The cobalt-chromium-molybdenum alloy powder and the cladding layer performance obtained in Examples 1-3 of the present invention were tested as follows by the following experimental instruments: 1. Powder composition: an X-ray fluorescence spectrometer was used to detect the main elements, an oxygen and nitrogen analyzer was used to detect O and N, a carbon and sulfur analyzer was used to detect C and S, and an ICP-OES was used to detect trace and trace elements; 2. Powder fluidity: a Hall flowmeter was used to measure the flow rate of the cobalt-chromium-molybdenum alloy powder; 3. Powder inclusions: a metallographic microscope was used to observe the powder non-metallic inclusions; 4. Sphericity: a metallographic microscope was used to observe and determine the powder sphericity; 5. Salt spray corrosion resistance: a salt spray tester was used to carry out a copper accelerated acetic acid salt spray corrosion test for 168 hours and a metallographic microscope was used to detect the number of pitting of the cladding layer; the specific test values are shown in Table 1.
[0051] Table 1 Physical properties and mechanical properties of powders for laser cladding
[0052]
[0053] As shown in Table 1, the cobalt-chromium-molybdenum alloy powder for laser cladding of the present invention has low oxygen, nitrogen and hydrogen content, few non-metallic inclusions, good fluidity (<15), and high sphericity (>90%), which makes the powder feeding uniform during laser cladding, the cladding layer uniform in structure, small in porosity, and dense in structure, thereby improving various properties of the cladding layer, especially the corrosion resistance, especially the Cl - Excellent corrosion resistance.
[0054] In summary, the cobalt-chromium-molybdenum alloy powder of the present invention has a lower cost by increasing the elements and their reasonable percentages. At the same time, the purity of the cobalt-chromium-molybdenum alloy powder prepared by the alumina crucible ingredients is improved by a suitable preparation method, and the contents of inclusions and oxygen, nitrogen and hydrogen in the powder are reduced. The powder has fewer inclusions, excellent fluidity, high sphericity, excellent physical properties, especially excellent corrosion resistance, and extended service life of the product after cladding.
Claims
1. A cobalt-chromium-molybdenum alloy powder for laser cladding, characterized by: The mass percentage of its chemical composition is: Cr: 27.0-32.0%, Mo: 4.0-6.0%, Fe: 7.5-9.5%, Y: 0.4-1.2%, Zr: 0.1-0.4%, and the balance is Co element and inevitable impurities.
2. The cobalt-chromium-molybdenum alloy powder according to claim 1, characterized in that: The contents of C, S, and P in the elements shall not exceed 100ppm, the contents of O and N shall not exceed 80ppm, and the content of H shall not exceed 10ppm.
3. The cobalt-chromium-molybdenum alloy powder according to claim 1, characterized in that: The mass fraction of Y+Zr is preferably: 0.6%≤Y+Zr≤1.1%.
4. The cobalt-chromium-molybdenum alloy powder according to claim 1, characterized in that: The mass fraction of Y+Cr is preferably: Y+Cr≥30.0%.
5. The cobalt-chromium-molybdenum alloy powder according to claim 1, characterized in that: The particle size ranges of the cobalt-chromium-molybdenum alloy powder are 45-105 μm, 53-150 μm, and 75-150 μm.
6. A method for preparing cobalt-chromium-molybdenum alloy powder, comprising the following steps: (1) Inert gas protection smelting; (2) Secondary charging; (3) Argon atomization; (4) Air flow classifier crushing and screening; (5) Ultrasonic vibration screen screening.
7. The preparation method according to claim 6, comprising the following steps: (1) Inert gas protection smelting: high-purity electrolytic cobalt, molybdenum bars, chromium blocks, and pure iron bars are placed in an alumina crucible according to the mass percentage of alloy elements, and then evacuated to a vacuum degree of less than 10 Pa. The argon gas charging valve is opened until the pressure in the furnace reaches normal pressure to complete the replacement. The above operation is repeated twice before smelting begins; (2) Secondary feeding: Add high purity yttrium 10-15 minutes before the furnace is discharged, and add high purity zirconium 5-7 minutes before the furnace is discharged; (3) Argon atomization: using inert gas argon to atomize cobalt-chromium-molybdenum alloy powder; (4) Air flow classifier crushing and screening: Collect the powder and adjust the frequency of the air flow classifier. The feed frequency is 5.0 Hz, the first level is 24.0-28.0 Hz, and the second level is 9.1-11.1 Hz. The air flow classifier uses argon with a purity greater than 99.999%. The air flow classifier is used to screen out the powder with a size of +45 μm at the first level discharge port; (5) Vibration sieve screening: adjust the energy of the ultrasonic controller of the ultrasonic vibration sieve to 100%, select 150 mesh and 325 mesh, 100 mesh and 270 mesh, 100 mesh and 200 mesh sieves, pour the coarse powder in the first-level discharge port into the discharge port of the vibration sieve for screening, and the discharge speed is 20 g / s.
8. A laser cladding method for cobalt-chromium-molybdenum alloy powder, wherein the process parameters are: spot diameter 5 mm, laser power 2.4-3.0 kW, scanning rate 1100-1500 mm / min, powder feeding amount 40-45 g / min, and overlap rate 45-60%.
Citation Information
Patent Citations
Low-density and high-structure-stability cobalt-based high temperature alloy and preparation method thereof
CN108385010A
Cited By
Nickel-chromium-cobalt-molybdenum high-temperature alloy for additive manufacturing and preparation method thereof
CN122462513A